The Impact of Digital Marketplace Application Utilization on the Effectiveness of Tax Attorney Service Promotion: A Study of the Hukumku Legal Platform - Rudy Sondang Sinaga (Yayasan Sinergi Kawula Muda, 2026)
This study analyzes how utilizing marketplace application features influences the promotional effectiveness of tax attorney services on the Hukumku platform. The primary focus is to test whether optimizing digital features improves measurable promotional outcomes. The study’s urgency lies in integrating professional legal service dynamics into digital marketplace theory, specifically regarding high-trust tax consultancy. This research employs a quantitative explanatory approach. The researcher operationalizes marketplace utilization through four dimensions: service searchability, profile information quality, chat-based interaction, and social proof. Meanwhile, promotional effectiveness is measured via brand awareness, lead quality, response rate, and conversion to paid consultations. Data were collected through a survey of 103 Hukumku users. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that marketplace utilization has a strong, positive, and significant effect on promotional effectiveness (β = 0,800; t=18.272; p < 0.001). An R2 value of 0.640 indicates substantial explanatory power within this model. These findings prove that strengthening digital trust-building mechanisms accelerates client purchase decisions. Empirically, this research extends technology acceptance perspectives to the tax attorney context. Practically, the results serve as a guide for professionals to enhance credibility signals and conversion performance on digital platforms. While the results are robust, behavioral generalizability is limited by the cross-sectional design and the use of self-reports on a single specific platform.